Effect of Trapping Method on Leukocyte Profiles of Black-Chested Spiny-Tailed Iguanas (Ctenosaura melanosterna): Implications for Zoologists in the Field. (12th September 2011) - Davis, Andrew K.; Ruyle, Leslie E.; Maerz, John C.
Abstract : When wild animals are captured for zoological research, researchers must choose a method of capture, and often this can be some form of passive, baited cage trap, or a direct capture with nets or nooses. If information on basal levels of circulating leukocytes is a goal, these two methods may provide different information, since recent evidence indicates that animals that enter cage traps experience stress, and, elevated stress hormones are known to alter leukocyte numbers in circulation by lowering lymphocyte and raising heterophil numbers. We tested this idea using a study of Black-chested Spiny-tailed iguanas ( Ctenosaura melanosterna ), which were captured using cage traps (n = 23 ) and noose (n = 27 ). Based on cell counts made from blood smears, iguanas caught with cage traps had significantly greater relative and absolute numbers of heterophils and higher heterophil-lymphocyte (H-L) ratios than those captured by noose. Cage-trapped animals also had a nonsignificant reduction in lymphocyte numbers. Similar trends were observed in animals captured with both methods. These patterns are consistent with the effects of stress hormones on white blood cell distributions and indicate that caution must be taken in interpreting leukocyte data from studies of wild animals captured with cage traps.